Notch1 activates angiogenic regulator Netrin4 in endothelial cells. Issue 5 (19th February 2019) - Liu, Qiang; Allen, Thaddeus D.; Song, Wei; Wada, Youichiro; Lobe, Corrinne G.; Liu, Ju
Abstract: Netrin4 (NTN4) is a chemotropic factor that regulates angiogenesis. We found that endothelial expression of the activated, intracellular domain of Notch1 (NICD1), significantly up‐regulated NTN4 mRNA as well as intracellular NTN4 protein in both transgenic mice and cultured human umbilical vein endothelial cells (HUVECs). Notch1 activation also increased NTN4 secretion from HUVECs. We subsequently demonstrated that NICD1 bound to CSL (CBF1, Suppressor of Hairless, Lag‐1), a core component of Notch transcription complex, at the −53 element of the human NTN4 gene promoter. Loss of the −53 element compromised NICD1‐induced NTN4 expression. Our results suggest a conserved role for Notch signalling in transcriptional regulation of endothelial NTN4 .